Comparison of the Effect of Strength Training With and Without Blood Flow Restriction on Motor Function in Active Females With Dynamic Knee Valgus - Seyyedeh Mahshid Hadavi; Parisa Sedaghati; Mohammad Mottaghitalab (Biyumikānīk-i varzishī, 2020)
Objective: Dynamic Knee Valgus is a common risk factor for acute lower extremity injuries and overuse. Studies on new training methods to improve motor function and strengthen the knee and thigh joint muscles are also ongoing. The purpose of this study was to compare the effect of conventional resistance training with and without Methods: This study was quasi-experimental. The present study’s statistical population consisted of active women with dynamic valgus deformity of the knee in Chalous (Mazandaran Province, Iran) aged 18-28. Thirty-six women with dynamic knee valgus were purposefully selected as the research Participants. Subjects were evaluated for patellar orientation with a goniometer, static and dynamic balance through stork and y tests, and lower limb strength with the Sargent jump test. Subjects were randomly divided into three groups: control, conventional resistance training without restricting blood flow, and traditional resistance training restricting blood flow. They also gave training sessions for 8 weeks in three sessions per week. Results: The results showed a positive effect of exercise programs on static balance (P=0.001), dynamic balance (P=0.001), patellar alignment, and lower limb strength (P=0.001) in women with dynamic knee defects. Also, the results of covariance analysis showed a significant difference between control and training groups. Conclusion: The present study results show a significant effect of the strength training program with and without restricting blood flow on improving patellar direction, static and dynamic balance, and lower limb strength of active women. It seems that active women can use these exercise programs to improve performance and reduce injury risk.